Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques